Plant nucleoside N-ribohydrolases: riboside binding and role in nitrogen storage mobilization - Ľuptáková, Eva; Vigouroux, Armelle; Končitíková, Radka; Kopečná, Martina; Zalabák, David; Novák, Ondřej; Salcedo Sarmiento, Sara; Ćavar Zeljković, Sanja; Kopečný, David Jaroslav; von Schwartzenberg, Klaus; Strnad, Miroslav; Spíchal, Lukáš; et al. (The Plant journal, 2024)
Cells save their energy during nitrogen starvation by selective autophagy of ribosomes and degradation of RNA to ribonucleotides and nucleosides. Nucleosides are hydrolyzed by nucleoside N-ribohydrolases (nucleosidases, NRHs). Subclass I of NRHs preferentially hydrolyzes the purine ribosides while subclass II is more active towards uridine and xanthosine. Here, we performed a crystallographic and kinetic study to shed light on nucleoside preferences among plant NRHs followed by in vivo metabolomic and phenotyping analyses to reveal the consequences of enhanced nucleoside breakdown. We report the crystal structure of Zea mays NRH2b (subclass II) and NRH3 (subclass I) in complexes with the substrate analog forodesine. Purine and pyrimidine catabolism are inseparable because nucleobase binding in the active site of ZmNRH is mediated via a water network and is thus unspecific. Dexamethasone-inducible ZmNRH overexpressor lines of Arabidopsis thaliana, as well as double nrh knockout lines of moss Physcomitrium patents, reveal a fine control of adenosine in contrast to other ribosides. ZmNRH overexpressor lines display an accelerated early vegetative phase including faster root and rosette growth upon nitrogen starvation or osmotic stress. Moreover, the lines enter the bolting and flowering phase much earlier. We observe changes in the pathways related to nitrogen-containing compounds such as β-alanine and several polyamines, which allow plants to reprogram their metabolism to escape stress. Taken together, crop plant breeding targeting enhanced NRH-mediated nitrogen recycling could therefore be a strategy to enhance plant growth tolerance and productivity under adverse growth conditions.
Keywords: Plants; Zea mays; purine; polyamine; Nitrogen; dusík; cytokinin; Nucleosides; nukleosidy; Uridine; nitrogen starvation; nucleoside N-ribohydrolase; overexpression; Arabidopsis; Physcomitrella patens; uridin; šlechtění rostlin; crystal structure; Plant Breeding; rostliny